Measurement Of Low Frequency Signal Of Power Grid Using Arduino - Mohd Ab Halim, Mohd Firdaus; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Ahmad, Suziana; Che Hasan, Mohd Hanif (2015)
The range of the frequency to be measured by a measurement device depends on the purpose of performing the measurement. The frequency measurement device is built specifically according to its range while the price of the device is proportional to its functions. In this paper, a low frequency measurement device to monitor grid frequency is designed using Arduino technology. All aspects of the design from the software to hardware is explained. This device costs less than 100 US Dollar and it is capable to perform data logging for data analysis. The frequency range for the device is between 45 Hz to 60 Hz with 0.003 Hz resolution. This paper also discuss the standard commercial measurement device in power system and Arduino capabilities. The measurement data from the device is analyze for its accuracy and reliability.